Detection and evaluation of a ventilation path in a mountainous city for a sea breeze: The case of Dalian. (November 2018) - Guo, Fei; Zhang, Hongchi; Fan, Yue; Zhu, Peishen; Wang, Shiyuan; Lu, Xiaodong; Jin, Yun
Abstract: In this study, an urban morphological method is introduced to detect ventilation paths to drain sea and mountain breezes to mitigate the urban heat island of Dalian, a typical coastal mountain city. Wind analysis shows that the dominant wind direction is south in summer, and north in winter; the wind is weak at night in the summer and autumn when mountain breezes could blow. The hindering effect of the mountain is included in the frontal area index calculation, and a reduction coefficient for the mountain's FAI is also presented in consideration of the differences of its shape from the building. Ventilation paths for both sea and mountain breezes are identified by mapping the frontal area index and the least cost path methodology based on a geographic information system (GIS) in a 100 m × 100 m grid. Four paths for south and four for north sea breezes are detected. The mountain breeze has a pattern similar to the sea breeze, but with several NW-SE direction paths. An advanced computational fluid dynamic model and field measurements are used to verify the wind paths detected. Field measurements are conducted to obtain air temperature, which average values are used to generate a temperature field in the GIS system. Corresponding planning mitigation policies are proposed according to the superimposed results of the least cost paths and air temperature field. Based on these findings, local governments and urban planners can improve living quality in the urban area. Highlights: The mountain's hindering effect was considered in frontal area index by regarding the study area as an obstacle cluster. A reduction coefficient for the mountain was presented to embody the difference between mountains and buildings. The ventilation paths were detected by least cost path method and verified by numerical simulation and field measurements. Mitigation policies were proposed according to an air temperature map superimposed by ventilation paths.